(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
In this article, it is shown that reading is a complex and multifaceted concept, a necessary attribute of human spiritual existence in the form of a self-organizing synergistic phenomenon. It is stated that it exists.